Thymic changes due to leishmaniasis in dogs: An immunohistochemical study - Jussiani, Giulia Gonçalves [UNESP]; Março, Karen Santos [UNESP]; Bertolo, Paulo Henrique Leal [UNESP]; de Oliveira Vasconcelos, Rosemeri [UNESP]; Machado, Gisele Fabrino [UNESP] (Elsevier, 2022)
Background: The thymus is necessary for the differentiation of T cells, a process that is regulated by the type of antigens found in thymocytes, the environment of surrounding cells and the thymus architecture. There is evidence that infectious diseases may result in morphological changes in this organ, such as premature atrophy and decreased thymocyte proliferation, that can affect the immune response. Objectives: We characterised the morphology and tissue distribution of haematopoietic and stromal cells in the thymuses of dogs naturally infected with Leishmania infantum, with the aim to determine the changes that may contribute to the pathophysiology of the disease. Methods: Thymus samples were collected from 15 animals (aged 6 months to 5 years) ELISA-positive for leishmaniasis and from 10 dogs from non-endemic regions for leishmaniasis whose death was not related to infectious causes. The samples were submitted to histological processing and staining with Haematoxylin-Eosin to assess thymic morphometry and histopathological changes. Masson's trichrome staining was used to quantify the connective tissue present (collagen). The immunohistochemical method was used to determine the cellular constitution of the thymus, using antibodies that aimed at marking T lymphocytes (anti-CD3), B lymphocytes (anti-CD79a), macrophages (anti- MAC387), mesenchymal cells (anti-vimentin), epithelial cells (anti-cytokeratin), cells in mitosis (anti-Ki67) and cells in apoptosis (anti-caspase-3). Results: The histopathological evaluation of infected dogs showed more signs consistent with thymus atrophy, including decreased parenchyma, infiltration of adipose and connective tissue near the capsule and between the lobules, lymphoid rarefaction mainly in the cortical region and loss of the cortical-medullary demarcation. In addition, we observed a decrease in the amounts of CD3 + T lymphocytes, macrophages (MAC387) and Ki67-positive cells and an increase in the number of cells positive for cytokeratin and CD79a (B lymphocytes). Finally, the parasite was detected in 46% of infected thymuses and may contribute for the observed changes. Conclusions: Apparently, leishmaniasis, like other infectious diseases, causes atrophy of the thymus and depletion of thymocytes with a relative increase in thymus epithelial cells. These morphological changes in the normal organisation of the thymus by mechanisms not yet well known may result in the abnormal release of T cells, with consequent damage to the host's immune response.
Keywords: Histopathological changes; Immunohistochemistry; Thymus atrophy